THE ROLE OF SALIMAH MASS ORGANIZATION IN BUILD THE FAMILY RESILIENCE (CASE STUDY IN CIMANGGIS SUB-DISTRICT, WEST JAVA, 2019-2022) - Syahidah, Izzah Asy; Imamuddin, Basuni (International Review of Humanities Studies, 2024)
Weak family resilience can cause various problems for family or society. Ideally, building family resilience is also needed society support. It will be more efficient if there is a place where people work together, such as a mass organization. One of the organizations that has contributed in building family resilience is Salimah (Muslimah Association). It is a mass organization of Indonesian Muslim women that focuses on providing solutions to improve the quality of women, children, and families. Salimah has many programs aimed at building family resilience. This study aims to examine Salimah’s role in building family resilience in Cimanggis sub-district, Depok, West Java, during 2019-2022. This research is descriptive qualitative research with literature study and interview methods. This study finds that Salimah’s role includes holding online seminars, conducting studies for majelis taklim, organizing business-related training for women, conducting patient visits to hospitals, distributing aid and donations, conducting workshops for ustadzahs, forming routine study groups for mothers, providing Al-Qur'an class for women, forming communities, and providing marketplace for housewives’ entrepreneurs. These roles are Salimah's works to fulfill the five dimensions of family resilience, namely the foundation of legality and family integrity, economic resilience, physical resilience, social psychological resilience, and socio-cultural resilience.